Control of Sectioning Distributed Power Grids with Renewable Energy Sources - Lezhniuk, P. D.; Rubanenko, O. O.; Hunko, I. O. (Visnyk of Vinnytsia Politechnical Institute, 2020)
A sign of today is the rapid pace of development of renewable energy facilities in the world and in Ukraine in particular. As for the Vinnytsia region, it occupies a leading position in the construction of photovoltaic power plants (PPPs). PPPs connect directly to the buses of the distribution power grids (DPGs), that designed under the conditions of centralized power supply. In this way, the radial line is converted to a double-sided line. Therefore, there are problems with the optimization of circuits and power flows in it to improve the reliability of electricity supply to consumers, improve the quality of electricity. This paper is the proposed method of control the generation of PPPs and small hydropower plants (HPP) in order to reduce the power losses in the DPG. It is proposed to control the power flows so that the calculated flow point in the transmission line corresponds to the sectioning point in it, by changing the generation capacity of the available managed renewable energy sources (RES) — HPP. The authors have also developed and described the capabilities of Intelligent Support for Distribution Power Grids Manager software, which makes it possible to determine which of the existing switchgear is appropriate to open circuits in the RES DPGs. It is shown how this software allows investigating the possibility of shifting the flow point to the node where the switchgear is installed to reduce the power loss by changing the power generation of the hydroelectric power plants and/or PPPs. The program also provides a message to the DPGs dispatcher in case the mode parameters deviate from their normalized values. The program is integrated into an automated system for controlling the generation of HPPs.